2021
DOI: 10.1111/os.12997
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy for Anterior Tibial Plateau Fractures in Hyperextension Knee Injuries

Abstract: Objective The aim of the present study was to summarize the clinical characteristics, treatment strategies, and clinical results for anterior tibial plateau fractures caused by hyperextension injuries. Methods We performed a retrospective analysis of 26 cases of anterior tibial plateau fractures that were treated with open reduction and internal fixation from January 2016 to December 2019, including 16 men and 10 women, aged 26–68 years old, with an average age of 47 ± 12.5 years. According to the three‐column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
0
14
0
5
Order By: Relevance
“…According to the ROBINS-1 assessment tool 41 , 5 studies 16,23,25,26,40 were with a moderate risk of bias, 11 studies 6,17,19,24,27,28,30,31,36,37,39 were rated with a serious risk of bias, and 13 studies 2,7,8,18,20-22,29,32-35,38 were rated with a critical risk of bias (Appendices 1 and 2; http://links.lww.com/JBJSREV/A970). Twelve studies did not report the underlying diseases of the patients, which raises some concerns about adjusting confounding factors 2,6-8,17-22,24,27-39 . This was rated as raising some concerns.…”
Section: Resultsmentioning
confidence: 99%
“…According to the ROBINS-1 assessment tool 41 , 5 studies 16,23,25,26,40 were with a moderate risk of bias, 11 studies 6,17,19,24,27,28,30,31,36,37,39 were rated with a serious risk of bias, and 13 studies 2,7,8,18,20-22,29,32-35,38 were rated with a critical risk of bias (Appendices 1 and 2; http://links.lww.com/JBJSREV/A970). Twelve studies did not report the underlying diseases of the patients, which raises some concerns about adjusting confounding factors 2,6-8,17-22,24,27-39 . This was rated as raising some concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Depression fractures are common in the tibial plateau and are caused by high-energy trauma. The most frequent mechanism is the hyperextension of the knee which leads the femoral condyle to cause axial compression on the anterior tibial plateau [ 1 ]. But to date, no case of depressed fracture of the metadiaphysis of tibia without the involvement of the articular surface has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Depressed fractures of the tibial plateau are common and are caused by high-energy trauma [ 1 ]. The case we are presenting involves an unusual focal depression fracture of the proximal tibial metaphysis without any articular involvement and without any underlying bone pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperextension bicondylar tibial fracture is a speci c type of tibial plateau fracture with a low incidence of approximately 11% of all tibial plateau fractures [2]. The impact of hyperextension on the knee joint leads to fractures of the anterior rim of the tibia along with signi cant ligament injuries [3]. Currently, only a few studies have been conducted on hyperextension injury of the knee since it was rst reported in 1977 [4].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of the hyperextension form of tibial plateau fractures involves reducing and xing the fractures and repairing ligament injuries, which restores the stability of the knee joint. However, there is no consensus on the ideal choice of surgical approach and fracture xation strategy [3], some authors have demonstrated and published a variety of options including a single midline incision or medial and lateral dual incisions to expose the fracture, anteriorly placed implants as well as medial and lateral dual plates to address the fracture [5,6,9]. Moreover, structural augments including tricortical iliac crest, bular allograft or spinal cage is recommended when the anterior metaphyseal void is greater than 1cm after restoring the posterior slope of the tibia [5].…”
Section: Introductionmentioning
confidence: 99%